Effectiveness Test of Tagetes erecta L Powder and Cattle Urine Waste that Potentially Repelent ont Boring Pests of Nezara viridula Pods in Soybean (Glycine max L) in Patumbak Subdistrict, Deli Serdang, North Sumatra - Rini Susanti; Andini Hanif; Lisdayani (Jurnal Pertanian Tropik, 2019)
Soybean plants (Glycine max) are the third most important food commodity crop after rice and corn. Soybean production continues to be improved in meeting community needs, but efforts to increase soybean production still face problems, namely green ladybird pest (N. viridula L.). One alternative to control soybean pod sucking insects that are relatively safe, inexpensive, and easily obtained is the use of vegetable insecticides. Vegetable insecticides do not quickly cause pest resistance, are synergistic, and their use can be combined with other pest control techniques. One of them is by using Tagetes erecta plants combined with cow urine as a vegetable insecticide. The use of repellents generally does not directly kill insects, but rather serves to reject the presence of insects, mainly due to the pungent smell. The use of cow urine as a mixture of biopesticides contains growth stimulants and contains repellents for several types of insect pests. This study aims to determine the effectiveness of Tagetes erecta in reducing the population of N.viridula pests in soybean plants (Glycine max L.Merr). Non Factorial RAK with 5 levels of treatment and 5 replications. Hopefully with this study farmers can take advantage of tagetes erecta and cow urine waste that can be used as natural pesticides and can be used as a control for Hama Nezara viridula which is environmentally friendly and economic.